Kryzys w kulturze, wartości estetyczne i teatralizacja życia politycznego według Hannah Arendt - Rogoziecki, Robert (Studia z Historii Filozofii, 2025)
The text concerns the issue of aesthetic values in Hannah Arendt’s Lectures of Kant’s Political Philosophy. Arendt considered the power of judgement a political ability. Her diagnosis of the state of crisis in European culture is the background for this statement. Her response to this is the postulate to develop our power of judgement as the basis of political community. This is possible thanks to a number of similarities between political activity and fine art. The problem is that Arendt, in her reflections on beauty as a political value, got entangled in contradictions and treated Kant’s Critique with carelessness. One of them, discussed in this essay, was the failure to take into account the importance of the sublime as an aesthetic value of key importance for politics and judgements about it. If politics were considered through the concept of the sublime, most problems the reader can find in Arendt’s Lectures would disappear, especially thenegligence of moral dimension of Kant’s political philosophy. Moreover, Arendt’s remarks concerning mass culture, expressed in the text The Crisis in Culture, seem to be fundamentally inaccurate. Taking into account Kant’s concept of the sublime allows a more correct recognition ofmass culture, its functioning and critical potential.